Some Wilker and Cusa type inequalities for generalized trigonometric and hyperbolic functions - Huang, Li-Guo; Yin, Li; Wang, Yong-Li; Lin, Xiu-Li (Journal of inequalities and applications, 2018)
The authors obtain some Wilker and Cusa type inequalities for generalized trigonometric and hyperbolic functions and generalize some known inequalities.The authors obtain some Wilker and Cusa type inequalities for generalized trigonometric and hyperbolic functions and generalize some known inequalities.